2017
DOI: 10.1617/s11527-016-0991-5
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage mechanisms of novel geometrical hooked-end steel fibres

Abstract: This study is aimed at fully understanding the anchorage mechanisms of steel fibres with novel hook geometries, e.g. 4DH and 5DH fibres, which were subjected to pull-out loading. The fibres were also embedded in four different matrixes with a compressive strength ranging from 33 to 148 MPa. The results showed that the anchorage and pull out behaviour was not only dependent on the geometry of the hooked end of steel fibres, but also closely related to the characteristics of matrix. Both maximum pullout load and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The typical picture of 3D, 4D, and 5D hooked fibers used in this study is shown in Figure 1. The 5D hooked-end steel fiber provided 11% and 73% higher maximum pullout load and 53% and 92% higher pullout energy than the 4D and 3D hooked-end steel fibers, respectively [10]. Such a superior bond performance is achieved because of the improved mechanical anchorage, owing to the increased number of hook ends.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The typical picture of 3D, 4D, and 5D hooked fibers used in this study is shown in Figure 1. The 5D hooked-end steel fiber provided 11% and 73% higher maximum pullout load and 53% and 92% higher pullout energy than the 4D and 3D hooked-end steel fibers, respectively [10]. Such a superior bond performance is achieved because of the improved mechanical anchorage, owing to the increased number of hook ends.…”
Section: Introductionmentioning
confidence: 94%
“…Owing to a better mechanical anchorage effect of the highly deformed hooked-end fibers, the order of bond performance was reported as follows: 5D > 4D > 3D [10]. Abdallah and Fan [10] noted that the maximum pullout load and energy absorption capacity of 5D hooked-end steel fibers embedded in normal-strength concrete are obviously higher than those of 3D and 4D fibers, respectively. In addition, three different volume fractions, i.e., 0.37%, 0.60%, and 1.00%, of hooked-end steel fibers were adopted to produce deflection-softening and deflection-hardening SFRCs, based on three-point bending test results [19].…”
Section: Research Objective and Design Process Of Novel Pedestrian Decksmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, Dramix hooked end fibres of 4D (double bend) and 5D (triple bend) geometries were developed specifically to increase the crack-bridging ability of SFRC. The high mechanical anchorage effect of these fibres was demonstrated in a number of prior studies showing that their strong bonding to the matrix resulted in a high resistance to pull-out (Abdallah and Fan 2017). Fibre with more a complex pre-deformed geometry place a higher complexity on the analysis of its pull-out response (Abdallah et al 2017c, d).…”
Section: Introductionmentioning
confidence: 98%